The conceivable benefits of being comprehensive – Finnish Local Education Authorities on recognising and controlling the social costs of school choice. (July 2015) - Varjo, Janne; Kalalahti, Mira
Since the 1980s, numerous education reforms have sought to dismantle centralised bureaucracies and replace them with devolved systems of schooling that emphasise parental choice and competition between increasingly diversified types of schools. Nevertheless, the Finnish variety of post-comprehensivism continues to emphasise municipal assignment of school places, in the form of the neighbourhood school principle ; albeit, in its current form, with the possibility for locally controlled choice and competition, channelled especially through classes with a special emphasis . Based on nine in-depth thematic interviews with experts in provision, management or evaluation of local level compulsory education, this paper focuses on how the conceivable costs and benefits of school choice are recognised and controlled in urban Finnish municipalities. Two distinctive discourses were found to be embodied in the portrayals of the costs and benefits of choice: the legitimization of school choice ; and promoting the comprehensive system . The legitimation of school choice discourse is built on the acceptable, but strictly limited reasons for choice, and necessity of school choice. In contrast, the discourse of fostering the comprehensive system is based on the ideology of equality of educational opportunities. It is constructed upon the traditional, universal, non-selective features of the comprehensive school. Against this background, possibilities for school choice can be, and must be, locally controlled – even restricted, if needed – in order to prevent a vicious circle of failing schools in deprived neighbourhoods.